MiR-92a promotes proliferation and inhibits apoptosis of prostate cancer cells through the PTEN/Akt signaling pathway. Issue 1 (1st January 2021) - Yanshen, Zheng; Lifen, Yang; Xilian, Wu; Zhong, Dong; Huihong, Mai
ABSTRACT: MicroRNAs (miRNAs) play an important role in the development of prostate cancer (PCa). Recent studies have shown that miR-92a expression is significantly increased in various cancers including PCa. However, its specific mechanism in PCa remains unknown. The goal of this study was to investigate the effect of miR-92a expression on the function and mechanism of PCa. PCa cell lines PC-3 and LNCap were transfected with miR-92a inhibitor to reduce the expression of miR-92a, respectively. The cell proliferation, cell viability, apoptosis, cell invasion and migration ability of PCa cells were examined by CCK8 assay, cell cloning, flow cytometry, Transwell assay and scratch assay, respectively. The effects of miR-92a on PTEN/Akt signaling pathway-related factors (PI3k, Akt, p-PI3k, p-Akt, PTEN) were also observed by RT-qPCR and Western blot. Compared with the control group and NC inhibitor group, the viability, cell migration and invasion ability of PC-3 and LNCap cells were decreased and apoptosis was significantly increased after interference with miR-92a expression. In addition, the mRNA and protein levels of PTEN in PC-3 and LNCap cells in the miR-92a inhibitor group were significantly increased, while the phosphorylation levels of PI3K and AKT were significantly decreased. MiR-92a might play a key role in regulating the proliferation, migration and invasion of PCa cells through the PTEN/Akt signaling pathway. Inhibition of miR-92a expression has practical value against PCa and provides ideas for further clinical treatment of patients with PCa.